Does Smoking Hamper Oral Self-Care Among Dental Professionals? - Ghasemi, Hadi (J Dent (Tehran), 2015)
OBJECTIVES: Smoking may impact oral self-care (OSC). This study aimed to analyze the role of smoking in OSC among Iranian dental health professionals. MATERIALS AND METHODS: The cross-sectional data were collected at two annual dental meetings and seven randomly selected dental schools in Iran. A total of 1,459 respondents composed of 967 general dental practitioners (GDPs), 229 dental educators (DE), and 263 senior dental students (DS) anonymously completed a self-administered questionnaire inquiring about smoking status and OSC. RESULTS: Thirty percent of the male and 12% of the female dental health professionals reported smoking tobacco. There was no difference between their professional status. Women reported better OSC than did men, but only 26% of the women and 17% of the men followed the three most important recommendations for OSC. Smoking was associated with infrequent tooth brushing and flossing, irregular use of fluoride containing toothpaste, consumption of sugary snacks and weak adherence to the recommended OSC guidelines. CONCLUSION: Dental health education should place more emphasis on smoking counseling and cessation among dental health professionals.